Pro Agile .NET Development with Scrum - Blankenship, Jerrel; Bussa, Matthew; Millett, Scott; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2011)
Pro Agile .NET Development with SCRUM guides you through a real-world ASP.NET project and shows how agile methodology is put into practice. There is plenty of literature on the theory behind agile methodologies, but no book on the market takes the concepts of agile practices and applies these in a practical manner to an end-to-end ASP.NET project, especially the estimating, requirements and management aspects of a project. Pro Agile .NET Development with SCRUM takes you through the initial stages of a project$1 (Bgathering requirements and setting up an environment$1 (Bthrough to the development and deployment stages using an agile iterative approach: namely, Scrum. In the book, you'll focus on delivering an enterprise-level ASP.NET project. Each chapter is in iterations or sprints, putting into practice the features of agile$1 (Buser stories, test-driven development (TDD), behavior-driven development (BDD), continuous integration, user acceptance testing, extreme programming, Scrum, design patterns and principles, inside-out development, lean developent, KanBan boards, and more. An appendix features code katas designed for the reader to get up-to-speed with some of the features of extreme programming, while also showcasing popular open-source frameworks to assist in automated testing and mocking. In addition, popular open-source architectural foundation projects such as S#arp and NCommons are demonstrated to allow you to base future projects on these frameworks, which already have many best-practice design patterns and principles built in.s
Keywords: Computer science; Computer Science; Computer Science, general; Electronic books